Подход к анализу информации с фитнесс-браслета - Моргун, М. К. (ХНУРЕ, 2019)
Health-monitoring tools are helping patients remember to take their medi-cations regularly and reducing the number of times they need to see their doctors. Public-health and medical researchers are employing wearable cameras and other mobile devices to analyze real-world physical activity and sedentary behavior patterns among certain populations, tapping into a much wider range of data than they could through traditional methods of sampling and recruitment. Wearable devices are expected to be particularly beneficial for under-served communities and individuals with serious, chronic health problems.
Keywords: mobil devices; wearable cameras; medical researchers